(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is an important sector of Indian economy as it is contributes about 17% to the total GDP and provides. Employment to over 60% of the population Indian agriculture has registered impressive growth over last few decades. Coffee production is the industrial process of converting the raw fruit of the coffee plant into the finished coffee. However, it is not what one would call a processed product. The cherry has the fruit or pulp removed leaving the seed or bean which is then dried. While all green coffee is processed, the method that is used varies and can have a significant effect on the flavour of roasted and brewed coffee. Coffee production is a major source of income, especially for developing countries where coffee is grown. By adding value, processing the coffee locally, coffee farmers and countries can increase the revenue from coffee. The coffee goes at least as far back as the 10th century, with a number of reports and legends surrounding its first use. The native (undomesticated) origin of coffee is thought to have been Ethiopia. The earliest substantiated evidence of either coffee drinking or knowledge of the coffee tree is from the 15th century, in the Sufi monasteries of Yemen. By the 16th century, it had reached the rest of the Middle East, South India, Persia, Turkey, Horn of Africa, and northern Africa. Coffee then spread to the Balkans, Italy and to the rest of Europe, to indonesia and then to America.